2013
DOI: 10.2337/db12-1095
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 Activates Skeletal Muscle AMPK and Reduces Weight Gain and Insulin Resistance in Mice

Abstract: Circulating interleukin (IL)-18 is elevated in obesity, but paradoxically causes hypophagia. We hypothesized that IL-18 may attenuate high-fat diet (HFD)-induced insulin resistance by activating AMP-activated protein kinase (AMPK). We studied mice with a global deletion of the α-isoform of the IL-18 receptor (IL-18R−/−) fed a standard chow or HFD. We next performed gain-of-function experiments in skeletal muscle, in vitro, ex vivo, and in vivo. We show that IL-18 is implicated in metabolic homeostasis, inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 34 publications
3
83
4
1
Order By: Relevance
“…It suggests the involvement of AMPK activation in the protecting effects of IL-37 against adipose tissue expansion on HFD feeding. Interestingly, recent data revealed that IL-18 signalling enhances FA oxidation via activation of AMPK signalling 45 . As both IL-37 and IL-18 bind to the same IL-18 receptor a chain (IL-18ra) 24 , our findings suggest that IL-37 can activate AMPK signalling via similar mechanisms, leading to increased FA oxidation and alleviation from development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests the involvement of AMPK activation in the protecting effects of IL-37 against adipose tissue expansion on HFD feeding. Interestingly, recent data revealed that IL-18 signalling enhances FA oxidation via activation of AMPK signalling 45 . As both IL-37 and IL-18 bind to the same IL-18 receptor a chain (IL-18ra) 24 , our findings suggest that IL-37 can activate AMPK signalling via similar mechanisms, leading to increased FA oxidation and alleviation from development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study also revealed that exendin-4 inhibited MC multiplication and expression of transforming growth factor-β1 and connective tissue growth factor, both of which induced ECM accumulation [15]. Exendin-4 induced phosphorylation of AMPK, which reduced weight gain and insulin resistance in mice with high-fat diets [16]. Additionally, phosphorylated AMPK was down-regulated in the kidneys of db/db mice [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, plasma IL-18 has also been positively associated with increased risk of insulin resistance and type 2 diabetes mellitus (T2DM) (Ahmad et al, 2013;Lindegaard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%